Borreliosis in horses: epidemiology, experimental infection and therapeutic - Basile, Roberta Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Lyme borreliosis is a disease caused by the spirochete Borrelia burgdorferi sensu lato, cosmopolitan and transmitted by the bite of ticks which remain adhered to the host for more than 24 hours. In humans, it can cause articular, cardiac and neurological diseases. In horses, so far the disease had been described by means of case reports and extrapolations of its pathogenesis in humans. This study aimed to investigate the clinical signs and hematological changes of Lyme disease in horses. Furthermore, it is also assessed the feasibility of treating infected horses with sodium ceftriaxone. To this end, the experiment consisted of three main phases. The first phase consisted of an epidemiological survey of the disease in São Paulo State, specifically in cities with suspected cases of Lyme borreliosis in humans. It was collected blood samples and clinical history of 760 horses that resulted in an average of 21% seropositivity in the state. In this stage, it was concluded that there was a high relationship between seropositivity, Amblyomma sculptum tick presence, the presence of capybaras in the property, lymphopenia, abortion and retained placenta. The second phase consisted of an experimental infection of two adult horses with B. burgdorferi strain G39 / 40. The horses were evaluated for 90 days of infection and we found that the animals showed nonspecific clinical signs and hematologic changes only in the first 11 days of infection. It was noted the presence of mild hypochromic normocytic anemia, muscle pain, pale mucous membranes, lethargy and swollen lymph nodes, signs that can easily be confused with chronic piroplasmosis. During phase 3 of the experiment, the two horses experimentally infected underwent treatment with intravenous sodium ceftriaxone. Already during the first application, both developed an anaphylactoid reaction moderate to severe with colic syndrome as consequence for one horse and laminitis to the other. Both recovered and were finally treated with oxytetracycline.

A Borreliose de Lyme é uma doença causada pela espiroqueta Borrelia burgdorferi sensu lato, cosmopolita, transmitida por meio da picada de carrapatos que permanecem aderidos ao hospedeiro por mais de 24 horas. Em humanos, pode provocar doenças articulares, cardíacas e neurológicas. Nos equinos, até o presente momento a doença havia sido descrita por meio de relatos de caso e extrapolações de sua patogenia nos humanos. Por meio do presente estudo, pretende-se pesquisar os sinais clínicos e alterações hematológicas da borreliose de Lyme nos equinos. Além disso, avaliou-se também a viabilidade de se tratar os equinos infectados com ceftriaxona sódica. Para tanto, o experimento foi composto por três principais fases. A primeira fase foi composta por um levantamento epidemiológico da doença no Estado de São Paulo, especificamente nas cidades com casos suspeitos de borreliose de Lyme em humanos. Coletou-se amostras de sangue e histórico clínico de 760 equinos e obteve-se média de 21% de soropositividade no estado. Desta fase, concluiu-se que existe grande relação entre a soropositividade, presença de carrapatos Amblyomma sculptum, presença de capivaras na propriedade, linfopenia, abortamento e retenção de placenta. A segunda fase foi composta por uma infecção experimental de dois equinos adultos com B. burgdorferi cepa G39/40. Os equinos foram avaliados durante 90 dias de infecção e foi possível verificar que os animais apresentaram sinais clínicos e alterações hematológicas inespecíficas somente nos primeiros 11 dias de infecção. Notou-se a presença de anemia normocítica hipocrômica discreta, dores musculares, palidez de mucosas, letargia e aumento de linfonodos, sinais que podem facilmente ser confundidos com a piroplasmose crônica. Durante a fase 3 do experimento, os dois equinos infectados experimentalmente foram submetidos ao tratamento com ceftriaxona sódica por via intravenosa. Já durante a primeira aplicação, ambos desenvolveram uma reação anafilactóide de moderada à severa, com consequência de síndrome cólica para um deles e laminite para o outro. Ambos se recuperaram e foram finalmente tratados com oxitetraciclina.
Borreliose em cavalos: epidemiologia, infecção experimental e terapêutica
Keywords: Borrelia burgdorferi; Tick; ELISA; PCR; Sodium ceftriaxone; Carrapato; Ceftriaxona sódica